The prevalence of traumatic events, posttraumatic stress disorder and posttraumatic stress symptoms among people seeking HIV testing - Sefatsa, Mpho Joyce (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.